Prevention of Targeted School Violence by Responding to Students' Psychosocial Crises: The NETWASS Program. Issue 1 (January 2017) - Leuschner, Vincenz; Fiedler, Nora; Schultze, Martin; Ahlig, Nadine; Göbel, Kristin; Sommer, Friederike; Scholl, Johanna; Cornell, Dewey; Scheithauer, Herbert
Abstract : The standardized, indicated school‐based prevention program "Networks Against School Shootings" combines a threat assessment approach with a general model of prevention of emergency situations in schools through early intervention in student psychosocial crises and training teachers to recognize warning signs of targeted school violence. An evaluation study in 98 German schools with 3, 473 school staff participants ( M age  = 46.2 years) used a quasi‐experimental comparison group design with three measurement points (pre, post, and 7 months followup) with schools randomly allocated to implementation conditions. The study found increases in teachers' expertise and evaluation skills, enhanced abilities to identify students experiencing a psychosocial crisis, and positive secondary effects (e.g., teacher–student interaction, feelings of safety).